2018
DOI: 10.1038/s41598-017-17981-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing human Treg immunotherapy by Treg subset selection and E-selectin ligand expression

Abstract: While human Tregs hold immense promise for immunotherapy, their biologic variability poses challenges for clinical use. Here, we examined clinically-relevant activities of defined subsets of freshly-isolated and culture-expanded human PBMC-derived Tregs. Unlike highly suppressive but plastic memory Tregs (memTreg), naïve Tregs (nvTreg) exhibited the greatest proliferation, suppressive capacity after stimulation, and Treg lineage fidelity. Yet, unlike memTregs, nvTregs lack Fucosyltransferase VII and display lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Interestingly, when studying Tregs divided in naive and memory Tregs, the association was mainly explained by memory Treg cells. The naive and memory Tregs have been shown to be two distinct subsets . Naive Treg cells derive from the thymus, whereas the production of memory Treg cells is induced peripherally .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, when studying Tregs divided in naive and memory Tregs, the association was mainly explained by memory Treg cells. The naive and memory Tregs have been shown to be two distinct subsets . Naive Treg cells derive from the thymus, whereas the production of memory Treg cells is induced peripherally .…”
Section: Discussionmentioning
confidence: 99%
“…While naive Tregs mostly originate from the thymus, memory Tregs are induced in the periphery and display the highest suppressive ability. 11,12 Insights into the biology of the cells that produce IgE are limited. In contrast to B cells expressing other Ig isotypes (IgM, IgD, IgA or IgG), IgE-expressing B cells are scarce and surface expression of IgE on these cells is low.…”
Section: Introductionmentioning
confidence: 99%
“…A recent clinical trial was initiated to test whether enforced fucosylation on CB Tregs infused prophylactically would improve homing and prevent GVHD in HSCT transplantation settings (Kellner et al unpublished findings). Recent evidence has confirmed that Tregs express fucosyltransferases, important enzymes in establishing fucose on siayl-Lewis x thus creating the CLA determinant on PSGL-1 [ 18 ]. The significant increase in CLA induced by the ex vivo culturing of CB Tregs in SCGM medium could supplant the need for exofucosylation of Tregs upon harvesting the expansion culture.…”
Section: Discussionmentioning
confidence: 99%
“…This is a milestone in optimizing the efficacy of human Treg immunotherapy by selecting functionally different subpopulations of Tregs and identifying the ideal source of Tregs. Thus far, > 40 Treg subpopulation divisions defined by different surface molecules have been reported (51,52).…”
Section: Division Of Treg Cells Into Three Functionally Different Submentioning
confidence: 99%